2019
DOI: 10.1108/jkm-05-2018-0288
|View full text |Cite
|
Sign up to set email alerts
|

Wisdom extraction in knowledge-based information systems

Abstract: Purpose This paper aims to provide a number of distinct approaches towards this goal, i.e. to translate the information contained in the repositories into knowledge. For centuries, humans have gathered and generated data to study the different phenomena around them. Consequently, there are a variety of information repositories available in many different fields of study. However, the ability to access, integrate and properly interpret the relevant data sets in these repositories has mainly been limited by thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…It is the information that is “understood,” associated with specific situations, and can guide “how” actions. The knowledge can be available in different formats, but analyzing, understanding, and categorizing it requires extra attention to convert it to wisdom ( Malik et al, 2018 ). In the era of information explosion, knowledge eliminates the false and preserves the true, eliminating the coarse and preserving the fine.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the information that is “understood,” associated with specific situations, and can guide “how” actions. The knowledge can be available in different formats, but analyzing, understanding, and categorizing it requires extra attention to convert it to wisdom ( Malik et al, 2018 ). In the era of information explosion, knowledge eliminates the false and preserves the true, eliminating the coarse and preserving the fine.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Through social networks, blogs, etc., dormant data on the Web flows in two directions (between users and data providers), making it easier for users to participate in and expand information and transform it into knowledge. However, the availability of information and the creation of knowledge/wisdom do not grow at the same speed ( Malik et al, 2018 ). That makes it more urgent to study how information can be more efficiently transformed into knowledge and wisdom, i.e., how this information is processed through their cognitive perspective to drive the decision-making process.…”
Section: Introductionmentioning
confidence: 99%
“…Howard Rheingold [26] described it as a "social aggregations that emerge from the Internet when enough people carry on public discussions long enough and with sufficient human feeling to form webs of personal relationships in cyberspace". Web 2.0 enable users not only to create and share information but also to convert it to knowledge [25]. In communities of practice, members use the knowledge shared to solve their own problems and share the solution with the community.…”
Section: Virtual Learning Community Of Practicementioning
confidence: 99%
“…One area of knowledge management could benefit from is machine learning. It was identified that machine learning could be beneficial to knowledge management, and its benefits must be looked at [16,17]. Machine learning algorithms can be used to further enhance a knowledge-intensive system [18].…”
Section: Introductionmentioning
confidence: 99%